2014
DOI: 10.14366/usg.13024
|View full text |Cite|
|
Sign up to set email alerts
|

Usefulness of ultrasound elastography in reducing the number of Breast Imaging Reporting and Data System category 3 lesions on ultrasonography

Abstract: Purpose:To evaluate the negative predictive value (NPV) of ultrasound (US) elastography for non-palpable Breast Imaging Reporting and Data System (BI-RADS) category 3 lesions on ultrasonography and to determine whether US elastography is helpful in reducing the number of BI-RADS category 3 lesions on ultrasonography.Methods:Two hundred seventy-six consecutive, non-palpable BI-RADS category 3 lesions in 256 women who underwent US elastography and US-guided core biopsy, and who had at least 12 months of follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…If we take a close look to our correlative analysis ( Fig. 2 , 3 , 5 ) it may be noted that the 1, 2 and BGR elasticity scores are mostly assigned to BI-RADS II and III benign lesions such as cysts, hamartomas, lipomas, hematomas, non-palpable fibroadenomas or mastopathic nodules – a result concordant with literature data [ 13 , 14 , 15 , 16 ]. In the enumeration above the cystic lesions classified as BI-RADS III ( Fig 8a ) or IV (1 palpable inflammatory cyst – Fig.…”
Section: Discussionsupporting
confidence: 88%
“…If we take a close look to our correlative analysis ( Fig. 2 , 3 , 5 ) it may be noted that the 1, 2 and BGR elasticity scores are mostly assigned to BI-RADS II and III benign lesions such as cysts, hamartomas, lipomas, hematomas, non-palpable fibroadenomas or mastopathic nodules – a result concordant with literature data [ 13 , 14 , 15 , 16 ]. In the enumeration above the cystic lesions classified as BI-RADS III ( Fig 8a ) or IV (1 palpable inflammatory cyst – Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The elasticity of breast masses is harder in malignant lesions than in benign lesions and harder in infiltrative breast malignancy than in in situ lesions, indicating that the negative predictive value of a negative elasticity score is 99.3% . Berg et al suggested that the maximum lesion diameter had a significant impact on maximum lesion stiffness ( P < .0001), with larger masses being stiffer than smaller masses for most histopathologic entities as assessed by shear wave elastography.…”
Section: Discussionmentioning
confidence: 99%
“…166 had negative elastograms with 1 of those patients having DCIS. If the negative elastograms were used to change the assessment from BI-RADS 3 to BI-RADS 2, in this cohort the malignancy rate would have changed from 1 to 1.8% [ 67 ]. Larger studies that include some invasive cancers in the BI-RADS 3 group are needed to validate these results.…”
Section: Ultrasound Bi-radsmentioning
confidence: 99%